2019
DOI: 10.1021/acs.joc.9b00923
|View full text |Cite|
|
Sign up to set email alerts
|

A Protonated Quinone Methide Stabilized by a Combination of Partial Aromatization and π-Interaction: Spectroscopic and Crystallographic Analysis

Abstract: We have expanded the repertoire of cation−π interactions to include a carbocation−π system resulting from the protonation of a π-stacked para-quinone methide (p-QM). This unusual carbocation is stabilized by a combination of partial aromatization of the QM moiety and through-space interaction with the π-system of the adjacent aromatic ring. Single crystal X-ray analysis of the protonated form reveals a structure consisting of a hydrogen-bound complex involving two molecules of the precursor and one proton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The photoreduced product 10 was isolated as the major product (18 mg, 0.04 mmol, 36% yield). Its characterization data were consistent with those reported in the literature …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The photoreduced product 10 was isolated as the major product (18 mg, 0.04 mmol, 36% yield). Its characterization data were consistent with those reported in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Our studies began with recently reported p -quinone methide ( p -QM) 1 , which displays a variety of unusual reaction chemistry. We photolyzed p -QM 1 at various wavelengths with the rather vague goal of inducing a dimerization reaction, known to happen in other quinone methides .…”
mentioning
confidence: 89%
See 3 more Smart Citations